Deterrents to participation in adult learning activities and literacy skills among seniors - Cloutier, Yvon J (University of Ottawa (Canada), 2003)
This study investigated the effect of variables that may influence the decision of seniors over the age of 60 not to participate in adult learning activities and literacy skills. Three research questions were of interest to the researcher. First, which of five socio-economic status (SES) variables (age, income, gender, employment status, education) are the best predictors of deterrents to participation in adult learning activities by seniors 60 years of age and over? Second, which of six deterrents to participation (lack of confidence, lack of course relevance, time constraints, low personal priority, cost, and personal problems) are the best predictors of participation in adult learning activities by seniors 60 years of age and over? Finally, is participation in adult learning activities by seniors 60 years of age and over a predictor of seniors' literacy skills? To measure seniors' reasons for not participating in adult learning activities, the Deterrents to Participation Scale-General was administered. Literacy skills were measured by the Tests of Applied Literacy Skills document literacy domain. To test the factors that were expected to affect non-participation, a survey questionnaire was administered to two groups, those who were currently participating in an organized adult learning activity and those who were not. Multiple regression estimates demonstrated that none of the regression lines could be plotted against any of the six deterrents to participation as criterion variables on the five SES variables as predictors. However, when the SES variables were held constant, only the effect of the variable employment status using the deterrents to participation lack of course relevance and low personal priority had a tendency to deliver the strongest explanatory power among all other predictor variables. Furthermore, regression estimates demonstrated that none of the six deterrents to participation had any effect on participation and that document literacy skills could not be predicted as a function of participation. In addition, the DPS-G showed low reliability estimates suggesting that the instrument needs to be revised taking into consideration other dimensions of deterrents to participation that are more relevant to seniors' lives.
Keywords: Gerontology.; Education, Adult and Continuing.